Barriers to inmate program participation in a private southern US prison. Issue 2 (15th March 2021) - Kaiser, Kimberly A.; Keena, Linda; Piquero, Alex R.; Howley, Caitlin
ABSTRACT: Annually, over half a million prisoners are released back into the community. It is important to identify and implement evidence-based strategies within prisons to aid in inmates' re-entry. An impressive knowledge base exists describing the effectiveness of these strategies, but much less is known about the barriers that impede participation in much needed programming. In this paper, we triangulate quantitative and qualitative data obtained from a sample of over 200 state prison inmates in a southern state. Our results show that there is significant interest in many pre-release programs among the inmates, but that several important barriers preclude their participation and/or continuation in these programs. Implications for policy are discussed.